ANALYSIS OF DAUD BEUREUEH'S THOUGHTS IN OPTIMIZING ISLAMIC RELIGIOUS EDUCATION IN ACEH: APPROACHES AND IMPLICATIONS - Azmi, Ulil; Ruhullah, Mohammad Eisa; Lismijar, Lismijar; Hadi, Abdul; Isa, M. (Journal of Higher Education and Academic Advancement, 2024)
Daud Beureueh was a reformer and influential figure in Aceh, who developed many principles and strategies for the development of Islamic religious education. His focus on the social and political context and his commitment to integrating Islamic values with relevant educational practices significantly influenced his approach to Islamic education. The purpose of the study was to determine the relevance, approach and implementation of Daud Beureueh's thoughts in Islamic religious education in Aceh. The research method used a qualitative method with a case study approach. The data collection method was carried out by in-depth interviews, observation and documentation studies. The research results show that 1). Daud Beureueh's thoughts are still very relevant in strengthening Islamic religious education in the modern era in Aceh, especially in facing the challenges of globalization and maintaining a strong local and Islamic identity. 2). The approach used by Daud Beureueh in Islamic religious education in Aceh shows a balance between tradition and modernity, between locality and nationality, and between spirituality and intellectuality. 3). The implications of Daud Beureueh's thoughts on Islamic religious education policies in Aceh reflect his commitment to forming a society that is not only academically superior but also solid in Islamic principles.